Structural and surface properties of polyvinylpyrrolidone and aloe vera - capped iron oxide nanoparticles: Application in the photocatalytic degradation of methylene blue - Njike, Rene; Yepseu, Adrien Pamen; Fotsop, Cyrille Ghislain; Doungmo, Giscard; Nchimi, Katia Nono; Ndifon, Peter Teke (European Journal of Chemistry, 2025)
Iron oxide nanoparticles were synthesized by the chemical precipitation method at 25 and 80 °C using polyvinylpyrrolidone (PVP) and aloe vera/polyvinyl pyrrolidone (AP) as capping agents. FTIR bands at 1584-1455 and 522-561 cm-1 confirm the formation of PVP- and AP-capped iron oxide nanoparticles. The formation of magnetite and hematite phases was confirmed by powder X-ray Diffraction patterns. The elemental composition of the synthesized particles was confirmed by EDX. SEM analysis revealed a mixed morphology of spherical and irregular-shaped particles of average crystallite sizes ranging from 9 to 58 nm, as estimated from XRD and SEM measurements. Both PVP- and AP-capped nanoparticles were used as catalysts for the photocatalytic degradation of methylene blue under ultraviolet (UV) irradiation. After 180 min of irradiation with 20 mg of photocatalyst, degradation efficiencies of 53-82% were obtained, with AP-capped nanoparticles being more efficient, suggesting their potential as effective materials for the photocatalytic degradation of toxic dyes in wastewater.